2019
DOI: 10.1002/smll.201902686
|View full text |Cite
|
Sign up to set email alerts
|

Friend or Foe? Evidence Indicates Endogenous Exosomes Can Deliver Functional gRNA and Cas9 Protein

Abstract: The clustered regularly interspaced short palindromic repeats (CRISPR)/associated nuclease (Cas) system is an efficient gene editing tool. In this study, it is found that both single guide RNA (gRNA) and Cas9 protein could be exported from the CRISPR/Cas9‐expressing cells by endogenous exosomes independently. Further experiments demonstrate that these naturally produced endogenous exosomes could be used as a vehicle to deliver the functional Cas9 and hepatitis B virus (HBV)‐specific gRNA to cut HBV DNA transfe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
61
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(69 citation statements)
references
References 54 publications
0
61
0
Order By: Relevance
“…The CRISPER/Cas9 system is a novel therapy for cccDNA clearance in CHB patients (Yang and Chen 2018;Kostyushev et al 2019). Recent studies have shown that exosomes isolated from CRISPR/Cas9 expressing cells contained functional single-stranded guided RNA (gRNA) and Cas9 protein (Chen et al 2019). These materials can be transferred to surrounding cells and further lead to the destruction of the HBV genome in cells Wang et al 2019).…”
Section: Exosomes As Novel Therapies For Hbv Infectionmentioning
confidence: 99%
“…The CRISPER/Cas9 system is a novel therapy for cccDNA clearance in CHB patients (Yang and Chen 2018;Kostyushev et al 2019). Recent studies have shown that exosomes isolated from CRISPR/Cas9 expressing cells contained functional single-stranded guided RNA (gRNA) and Cas9 protein (Chen et al 2019). These materials can be transferred to surrounding cells and further lead to the destruction of the HBV genome in cells Wang et al 2019).…”
Section: Exosomes As Novel Therapies For Hbv Infectionmentioning
confidence: 99%
“…Several studies described a number of reproducible and scalable strategies for transferring chemically modified RNAs (mostly siRNAs) into isolated EVs. In particular, a group led by Anastasia Khvorova demonstrated that modifying miRNA with docosanoic acid, cholesterol, or tocopheryl succinate led to the packaging of thousands of miRNAs into EVs [ 224 , 225 ]. Packaging efficiency and stability of packaged RNA were affected by siRNA chemical modification patterns, position of the hydrophobic moiety (5′ or 3′ strand), and the linker used to attach the moiety to siRNA.…”
Section: Packaging Crispr/cas Protein and Rna Components Into Evsmentioning
confidence: 99%
“…In Table 3, we summarize several methods for extracting exosomes and list their characteristics. [95], small molecule drugs [96], peptide ligands [97], and therapeutic RNA [98,99]. Researchers have used multiple methods to engineer exosomes for cargo delivery, including incubation with saponin, electrical stimulation, sonication [30]…”
Section: Engineering Exosomes As Nanocarrier Formentioning
confidence: 99%